Contribuição da Educação e da Psicologia: a Importância do vínculo afetivo entre auxiliares de desenvolvimento infantil e crianças da creche de 0 a 4 anos - Capelasso, Rosângela Regina Marcicano (2011)
Whereas the bonding relations are important for child development, resulting in the organization of the child´s personality and in structuring their relationships with others around them, the goal of this research is focused on the importance of bonding between the Auxiliary Child Development ACDs and children´ s nursery and the implications of this link to child development. We tried to also consider the qualification, the planning of teaching activities and teaching practice. The literature search was focused on authors with questions regarding some historical aspects of childhood; Historical aspects of the nursery, and some aspects of the theories about the physical, cognitive and psychosocial. The research was conducted under the qualitative perspective, specifically the type of case study. The methodological procedures involved: 1. Collecting data through interviews with a semi-structured, with eight assistants Child Development working in a nursery to the Public in the city of Presidente Prudente (SP), seeking information about the relationship of these affective eat children from 0 to 4 years. Were also used documents and observation, to enrich the discussion of results. 2. Analysis and discussion of data, worked through the interpretation of the meaning of the responses provided by subjects based on content analysis, which were separated by Main and categories, and related to the objectives proposed by the research. The results indicate that ACDs have teaching qualification to work in the nursery with children, seeking additional courses to qualify. It can be seen that the bonding between ACD within the nursery and children is a reality that has been proven through situations experienced and reported by them. One can also observe the kindergarten as a dynamic environment with respect to the evolution of changes, not only as a site for the care of children, but as an environment that promotes learning them. As for the professional development of the ADI, let me make a suggestion to seek more skilled, making Specializations in the area relevant to their work with children. Another suggestion would be to participate in the same events that they can collaborate with professional work developed, contributing to society, because if the ADI seek knowledge of other professionals will be better able to deal with day to day in the nursery. In this sense the experience summed and divided contribute to the learning of children, caregivers and society in general. The appreciation of the exchange of ideas, reflecting on the position of information among others are some attitudes that ADI should possess. Understand the facts that pervade this universe, people sensitive and yet so strong, I gave hope of better days, a relationship of harmony with life.